The [poky] mutant of Neurospora contains a 4-base-pair deletion at the 5' end of the mitochondrial small rRNA. - Akins, R A (1984)
[ poky ] and other group I extranuclear mutants of Neurospora crassa are characterized by gross deficiencies of mitochondrial small ribosomal subunits and small (19S) rRNA. Blot-hybridization and other experiments suggest that the 19S rRNA (2.0 kilobases) is synthesized via precursors that contain 5'-end extensions. The ratio of precursors to mature rRNA is higher in [ poky ] and other group I mutants than in wild type, indicating that the defect involves impaired processing and/or instability of 19S rRNA. [ poky ] and other group I mutants contain a 4-base-pair deletion in the coding sequence for the mitochondrial small rRNA, just downstream from what would normally be the 5' end of the rRNA. This deletion apparently results in synthesis of aberrant 19S rRNAs that are missing 38-45 nucleotides from their 5' ends. We propose that the 4-base-pair deletion is the primary defect in [ poky ] and other group I extranuclear mutants.